Oxidative Stress Mediates Vascular Tortuosity - Toshio Fumoto; Shouhei Kinoshita; Takao Sasaki; Norihito Shimamura; Hiroki Ohkuma (MDPI AG, 2021)
Vascular tortuosity is associated with various disorders and is being increasingly detected through advances in imaging techniques. The underlying mechanisms for vascular tortuosity, however, remain unclear. Here, we tested the hypothesis that oxidative stress mediates the generation of tortuous vessels. We used the bilateral common carotid artery (CCA) ligation model to induce vascular tortuosity. Both young and adult rats showed basilar artery tortuous morphological changes one month after bilateral CCA ligation. These tortuous changes were permanent but more pronounced in the adult rats. Microarray and real-time PCR analysis revealed that these tortuous changes were accompanied by the induction of oxidative stress-related genes. Moreover, the indicated model in rabbits showed that tortuous morphological changes to the basilar artery were suppressed by antioxidant treatment. These results are highly suggestive of the significance of oxidative stress in the development of vascular tortuosity. Although further studies will be needed to elucidate the possible mechanisms by which oxidative stress enhances vascular tortuosity, our study also points toward possible prophylaxis and treatment for vascular tortuosity.